2011
DOI: 10.1111/j.1467-7652.2011.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the F‐box gene LARGER PANICLE improve the panicle architecture and enhance the grain yield in rice

Abstract: Summary Panicle architecture is one of the most important agronomical traits that directly contribute to grain yield in rice (Oryza sativa L.). We report herein an in‐depth characterization of two allelic larger panicle (lp) mutants that show significantly increased panicle size as well as improved plant architecture. Morphological analyses reveal that panicles of two mutants produced more inflorescence branches, especially the primary branches, and contained more grains. Moreover, mutant plants also display m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(111 citation statements)
references
References 51 publications
2
108
1
Order By: Relevance
“…The Kelch domain has been reported to represent one β-sheet blade, and several repeats are able to interact to form a β-propeller (17). In rice, LARGER PANICLE (LP) encoding a Kelch repeat-containing F-box protein was reported to play a negative role in regulating plant architecture, particularly panicle architecture (18). In this study, we also found that the Kelch domains in OsPPKL1 93-11 play a negative regulation role in forming grain length.…”
Section: Resultsmentioning
confidence: 99%
“…The Kelch domain has been reported to represent one β-sheet blade, and several repeats are able to interact to form a β-propeller (17). In rice, LARGER PANICLE (LP) encoding a Kelch repeat-containing F-box protein was reported to play a negative role in regulating plant architecture, particularly panicle architecture (18). In this study, we also found that the Kelch domains in OsPPKL1 93-11 play a negative regulation role in forming grain length.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that Gn1a (OsCKX2), encoding a cytokinin oxidase/dehydrogenase that regulates grain number by degrading bioactive cytokinin in inflorescence meristems (22), was strongly selected in IndI. LARGER PANICLE (LP), a gene that encodes a Kelch repeat-containing F-box protein (23), was also found to be significantly selected in IndI. In connection with the previous report that two allelic lp mutants showed an increased panicle size with more grains, it was suggested that LP might also be a very important target for improvement in rice breeding.…”
Section: Significancementioning
confidence: 99%
“…The FBK proteins ZEITLUPE, FLAVIN-BINDING, KELCH REPEAT, F-BOX1, and LOV KELCH PROTEIN2 are involved in light signaling, flowering, and circadian control via a proteasome-dependent pathway in Arabidopsis (Imaizumi et al, 2005). The rice (Oryza sativa) FBK gene LARGER PANICLE/ERECT PANICLE3 was reported to regulate panicle architecture (Piao et al, 2009) and modulate cytokinin levels through Oryza sativa CYTOKININ OXIDASE2 expression (Li et al, 2011a). However, only a few substances for F-box proteins with specific functions are known in plants.…”
mentioning
confidence: 99%